Laku dan Fenomena Seks di Era Milenial - Kadek Agus Wardana; Kadek Ayu Kristini Putri; Ni Made Sukrawati; Ida Ayu Gde Yadnyawati (Sphatika: Jurnal Teologi, 2022)
Global life demands that one must think more critically and be more open to change. We cannot deny that an era of freedom is in front of our eyes. We cannot escape, the impact of that era has touched all dimensions of life, even the sexual dimension. If we are not able to think broadly about the changes that may occur in that dimension, then the law of natural selection will speak and eliminate those who are static. Fundamentally, the teaching of sexuality in Hindu religious teachings contained in classical literature in the form of Lontar is actually not a taboo teaching. This can be proven by understanding the teachings of Hinduism in an integral holistic manner. In writing this article, the method used is literature study by entering keywords on google.scholar.com and various other literatures to support the references of this article. In addition, several articles and/or books related to this theme also support the completion of this article. Many academics and religious leaders think that sexuality is an unusual thing to talk about or discuss, but Hinduism responds with a theory that refutes taboos in sexual matters. Sexuality is a very important thing to be discussed and analyzed as a form of a person's fundamental education to know in relation to sex or sexuality.